Quem produz os conhecimentos que circulam? Uma análise feminista e decolonial das revistas brasileiras sobre movimentos sociais - Mariane Silva Reghim (Ciências Sociais Unisinos)
The article presents two fronts of analysis. One is to understand if and in what way social movements appear as producers of knowledge. The other is to understand how gender and nationality are distributed between authorship and bibliographic reference of the objects analyzed here. To understand how these relations operate in the national circuit, the article relies on the analysis of three brazilian academic journals on social movements. This approach is justified by the fact that journals are a legitimate and easily accessible means of knowledge dissemination. The objective is to categorize the authors of the articles, as well as the bibliographic references used, according to their gender and nationality and also the type of material used as a reference. In terms of theoretical analysis, I am based on feminist (and) decolonial authors for providing reflections that consider the dynamics of gender and nationality as central axes of sociological analysis. As a result, I identified that, in general, publications by social movements are minimal, with the greatest participation of male authors. However, when making an analysis in terms of gender and nationality, the dynamics are altered, so that more Brazilian women are referenced, highlighting the nuances that are intrinsic to gender and nationality relations.